(untitled) (International Journal of Physiotherapy, 2020)
Background: The Timed up and Go Test (TUG) is often used as a mobility measure in older people. However, it is unclear whether the TUG is useful for identifying fall risk in people with diabetes mellitus (DM) and which physical and cognitive/psychological factors influence the performance of this test. Objectives: To investigate whether slow TUG times (standard test and when performed with a secondary cognitive task (c-TUG)) are a risk factor for falls in older people with DM and to determine the relative contributions of a range of sensorimotor, balance and cognitive/psychological factors to TUG performance in this population. Methods: Community-dwelling people (n=103, mean age 61.57, SD=6.3) underwent the TUG and c-TUG tests as well as quantitative tests of vision, peripheral sensation, strength, reaction time, balance, cognition, and fear of falling. Participants were then followed up for falls for six months. Results: Negative binomial regression analyses revealed that each 1s increase in TUG and c-TUG times increased the risk of falling by 29% and 13%, respectively. Multiple regression analyses identified vibration sense (p<0.001), knee extension strength (p=0.001, r²=0.430), edge contrast sensitivity (p=0.002), neuropathy examination score (p=0.001, r²=0.498) and controlled leaning balance (p=0.033) as significant and independent explanatory predictors of TUG performance. The regression model for c-TUG was similar, vibration sense (p=0.042), knee extension strength (p=0.009, r²=0.256), neuropathy examination score (p=0.156, r²=0.272) and sway path-floor (p=0.042) except that the MOCA cognitive assessment (p=0.015) was included instead of edge contrast sensitivity. The combined explanatory variable models explained 43% and 26% of the variance in TUG and c-TUG times, respectively. Conclusions: Slow TUG and c-TUG times significantly increased the risk of falls in community-dwelling older people with DM. Poor TUG and c-TUG performances were related independently to decreased vibration sense, lower limb weakness, and poor balance, with the c-TUG additionally influenced by cognitive function.